Effects of post-emergent herbicides on Trichoderma harzianum, a potential biocontrol agent against Sclerotinia sclerotiorum in soybean cropping - Rollán, María Cristina (2007)
Trichoderma harzianum is a potential biocontrol agent against Sclerotinia sclerotiorum in soybean. Information is needed on the compatibility of this biocontrol agent and the post-emergent herbicides used in soybean cropping. Haloxyfop R Methyl (EC 10.4%), Glyphosate (SL 48%), Imazamox (WG 70%) and Imazethapyr (SL 10%) were evaluated for their effects on the mycelial growth of T. harzianum on in vitro agar plates. Glyphosate (2000 ppm), Imazethapyr (500 and 250 ppm) and Haloxyfop R Methyl (1000, 500 and 100 ppm) reduced the mycelial growth of T. harzianum. Imazamox had no effect at any concentration. Subsequently, all the herbicides were assessed for their effect on soil populations of T. harzianum. Greenhouse assays conducted with non-sterile soil inoculated with T. harzianum and a specific herbicide were sampled before pesticide application and after 30 days. The number of colony forming units per gram of soil (c.f.u./g of soil) was evaluated with a soil dilution technique using Trichoderma selective medium (TSM). No detrimental effect was revealed.